Pendampingan Pastoral Terhadap Keluarga-Keluarga Kristen Yang Mengalami Masalah Perselingkuhan Di Jemaat Imanuel Klabat Wilayah Tatelu - Vera Burhan; Tania Suoth (PT. Giat Konseling Nusantara, 2026)
This research discusses Christian families who have problems with infidelity at the congregation of GMIM Bukit Sion Kanonang. These families vary from their 2nd, 20th, 24th, 31st, and 36th years of marriage. With various background and reason why they chose to have an affair. Obviously, this infidelity problem can not be left alone. That is why there needs to be a service to help the congregatin in maximizing pastoral assistance to those who are having problems in marriage life. In this research, the writer uses qualitative method with data collecting technique namely: observation, literature study, and interview with sampling technique (Purposive Sampling).